Faktor determinan proksi kejadian kematian neonatus di wilayah kerja dinas kesehatan kabupaten Buton Utara - La Ode Alifariki; Adius Kusnan; La Rangki (Berita Kedokteran Masyarakat (BKM), 2019)
Proxy determinant factors of neonatal mortality rate in the working area of North Buton District Health OfficePurpose: This study aims to determine the proxy determinant of the incidence of neonatal death.Methods: This type of research is observational analytic with a case control approach. The population is all neonatal born in the working area of North Buton District Health Office for the period of 2016-2018. Case samples were neonates who died before the age of 28 days while the control samples were neonates who lived to the age of 28 days with a sample size of 108, with a ratio of 1 case: 2 controls, the sample size was 36 and the control was 72 samples. Data collection is using a questionnaire. Data is processed using the SPSS 16.0 for Windows program to present data in the form of tables and narratives based on the variables studied. Data were analyzed using the test (OR) at the limit of significance α = 0.05.Results: Based on this study, it can be concluded that the risk factors for neonatal death in the working area of North Buton District Health Office are distance birth OR = 8,5 (3,334-21,668), antenatal care quality OR = 3,571 (1,522-8,380), delivery helper OR = 12,429 (4,788-32,259), neonatal sepsis / postnatal infection OR = 4,247 (1,785-10,063), accessibility OR = 4,545 (1,932-10,692), delay in deciding to seek help OR = 6,000 (2,441-14,751).Conclusion: The proxy determinant of neonatal death in the working area of North Buton District Health Office in 2018 was a delivery helper.